RANCANG BANGUN SISTEM INFORMASI MANAJEMEN ACARA BERBASIS WEB DENGAN MODEL WATERFALL (STUDI KASUS: ORGANISASI KEMAHASISWAAN UPN VETERAN JAKARTA) - Patrick Santino (2023)
Student organizations, known as ormawa in Indonesian, are organizations composed of students in a university. Ormawa serves as a platform for students to develop their skills through participation in various relevant events. The implementation of ormawa event organization within the environment of Universitas Pembangunan Nasional Veteran Jakarta, or UPN Veteran Jakarta, has not been running smoothly. The underlying cause of this statement is the lack of effective event support facilities. This issue has prompted researchers to design a web-based event management information system that can serve as a support tool for ormawa event organization at UPN Veteran Jakarta. The system development follows the Waterfall model, where each stage of system development depends on the output of the previous stage. The result of this research is a web-based event information system that can serve as a support tool for ormawa event organization within the UPN Veteran Jakarta environment